2013
DOI: 10.2174/1876827x01305010010
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effect of Gold or Silver Nanoparticles on Meiotic and Postmeiotic Fractions of Rat Germinal Cells

Abstract: The cytotoxicity of Au or Ag nanoparticles (NPs) on rat germinal cells was investigated in vitro. Rat germ cells separated by the STAPUT method in two different populations, pachytene spermatocytes (F5) and round spermatids (F3), were incubated (37°C, 60'-120') with 60 μM, 125 μM, 250 μM and 500 μM of Au/Ag-NPs. Cell viability was assessed with the Eosin Y test. Au or Ag-NPs were investigated with FEG-STEM/EDS and TEM. A dose-dependent effect on the viability of F3 and F5 populations was observed after incubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Other investigations have reported that as sperm mobility occurs in epididymis, inflammation of epididymis that is induced by nanoparticles exposure, could diminish sperm motility [1,[26][27][28][29]. Reportedly, sperm motility is probably reduced due to the impact of silver nano-particles on mitochondrial functions [30].…”
Section: Discussionmentioning
confidence: 99%
“…Other investigations have reported that as sperm mobility occurs in epididymis, inflammation of epididymis that is induced by nanoparticles exposure, could diminish sperm motility [1,[26][27][28][29]. Reportedly, sperm motility is probably reduced due to the impact of silver nano-particles on mitochondrial functions [30].…”
Section: Discussionmentioning
confidence: 99%